EFEKTIVITAS PEMBELAJARAN DARING BERBANTUKAN APLIKASI ZOOM MEETING UNTUK MENINGKATKAN HASIL BELAJAR SISWA SEKOLAH DASAR MASA PANDEMI COVID-19 - Niken Septantiningtyas; Siami Fitri Astutik; Muhammad Mushfi El Iq Mushfi El Iq Bali (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2022)
Abstract: The purpose of this study is to describe the effectiveness of online learning using zoom meetings on student learning outcomes. The research population is all fourth grade students of MI Mambaul Ulum Paiton Probolinggo who use zoom meetings during learning activities. The sample of this research is the fourth grade students of MI Mambaul Ulum Paiton Probolinggo as many as 33 students using simple random sampling technique. Data collection techniques in this study include field studies, observations, interviews, and questionnaires. The data collection instrument used a questionnaire containing the types of closed, semi-closed, and open-ended questions. Data analysis using computerized descriptive statistics. The results of the study revealed that the media platform used in online learning was dominated by the Zoom Meeting application (56.2%). During online learning, students experience physical complaints such as eye irritation (32.8%), while psychological complaints experienced by students are that they feel they are not really studying (37.2%). Furthermore, the online learning methods that students prefer include learning videos (35.1%) and quizzes (28.8%). Constraints experienced by students include unstable internet network (41.4%), limited quota pulses (26.5%), split learning concentration (13.3%), and piling assignments (17.6%). The accumulation of these data concluded that the assessment of the effectiveness of online learning experienced by students in detail was known with the criteria of very effective (14.6%), effective (58.7%), moderately effective (24.5%), and ineffective (2, 2%).